POETIC AND IDEOLOGICAL FEATURES OF “KITYA” OF ORZU URGANJI (TAMADDUN NURI JURNALI, 2024)
In the article the works of the poet Orzu Urganji, who lived and wrote poetry in the twentieth century are learned. Themes, ideas, artistic problems in them are given separately and carefully analyzed.